Correction to: Alleviation of 4-nitroquinoline 1-oxide induced oxidative stress by Oroxylum indicum (L.) leaf extract in albino Wistar rats - Shalini Mohan; Kalaivani Thiagarajan; Balaji Sundaramoorthy; Vivek Gurung; Manas Barpande; Shilpi Agrawal; Rajasekaran Chandrasekaran (BMC, 2022)
An amendment to this paper has been published and can be accessed via the original article.